Effects of Concentrate Supplementation on Performance Characteristics of Goats Challenged with Trypanosoma brucei - M. B, Yousuf; A. A, Adeloye; M. A, Belewu; A. O, Olatunde; Lawal, Muhammad; Azeez, Abdul; J. O., Daramola (Asian Journal of Agriculture and Rural Development, 2014)
The influence of concentrate-feed supplementation on dry matter and nutrient intake and digestibility, nitrogen retention and body weight gain in goats challenged with trypanosomiasis was studied. Sixteen male West African Dwarf (WAD) goats (7.32 ± 0.70 kg) inoculated with 1.5 × 106 Trypanosoma brucei were divided into four treatment groups each of four replicates in a 56-day, completely randomized design experiment. Treatments consisted of varying intake levels (0, 50, 100 and 150 g/head/day) of a maize-based concentrate supplement (19.72 %; CP) to basal Panicum maximum hay (10.81 %; CP). Dry matter intake (g/head/day) of 211.77 ± 2.66, 215.14 ± 7.25, 253.28 ± 5.23, and 275.96 ± 3.65 obtained for goats fed supplement at 0, 50, 100 and 150 g/head/day respectively were different. Coefficient of crude protein or crude fibre digestibility was higher (p < 0.05) for goats fed the concentrate supplement at 100 or 150 g/head/day level than for those fed at 50 g/head/day or the control. Differences in feed nutrient intake and digestibility caused gradual improvement (p < 0.05) in body weight gain (g/head/day) from 8.39 ± 0.21 in the un-supplemented group to 18.21 ± 0.42 in goats fed concentrate supplement at 150 g/head/day. The results indicated a positive influence of concentrate supplementation on ability of the goats infected with trypanosomiasis to consume and digest feed nutrients for body weight gain. The 100 g /head/day level of supplementation was considered adequate.